The Relationship between Psychological capital on Organizational Citizenship Behaviors Due to the Moderating Role of Conscientiousness in a Training Public Sector Organization - Mohsen Golparvar; علی فتحی (Pizhūhish/hā-yi rahbarī va mudīriyyat-i āmūzishī, 2015)
This study aimed to investigate the relationship between psychological capital components (self-efficacy, hope, resiliency and optimism) and organizational citizenship behaviors due to the moderating role of conscientiousness. Research statistical population was the employees of a public sector organization in Ahvaz city. From the statistical population mentioned above, two hundred seventy nine persons were selected by convenience sampling. Research instruments were psychological capital questionnaire (Nguyen et al, 2012), organizational citizenship behaviors questionnaire (Lee & Allen, 2002) and conscientiousness questionnaire (De Nevea & Oswald, 2012). Data were analyzed with the use of Pearson correlation coefficient and hierarchical regression analysis. Results revealed that, there is a positive significant relationship between psychological capital and organizational citizenship behaviors. Also the results revealed that there is a positive significant relationship between psychological capital and conscientiousness and between conscientiousness and organizational citizenship behaviors. The results of moderated hierarchical regression analysis indicated that conscientiousness has been moderates the relationship between self-efficacy and hope with organizational citizenship behaviors toward individuals. Also conscientiousness has been moderates the relationship between self-efficacy and organizational citizenship behaviors toward organization